State of Professional Preparation of Future Physical Training Teachers to Teach Swimming at Children's Holiday Camps - C. М. Клімакова (OVS LLC, 2016)
The paper reviews the state of professional preparation of future physical education teachers relying on the comparison of the fundamental documents that shape the professional competence of a swimming instrucror at children's holiday camps. The author analyzes and compares the compliance of the educational-qualification standard in the physical education speciality with the requirements of the swimming instructor's professional duties at children's holiday camps. The paper compares the compliance of the swimming curricula of the School of Physical Education of H. S. Skovoroda Kharkiv National Pedagogical University with the educational-qualification standard in the physical education speciality and the requirements of the swimming instructor's professional duties at children's holiday camps.